Pembelajaran Menulis Resensi Novel Berbantuan Media Wattpad - Ambarwati, Sindi; Ulfah, Anisa; Ihsan, Bisarul (Universitas Sebelas Maret, 2025)
The learning of novel review writing in class XI of SMA Ahmad Yani 2 Baureno was considered less effective because it still relied on the lecture method. Therefore, the researcher used the Wattpad application as an alternative learning medium. The purpose of this study is to find out how the planning, implementation, and student learning outcomes occur in novel review writing learning assisted by the Wattpad media. This type of research is qualitative. The research sample consisted of class XI students of SMA Ahmad Yani 2 Baureno, totaling 26 students. The sampling technique used in this study was total sampling, in which all 26 students of class XI were taken as the sample because the number was relatively small and allowed for a comprehensive investigation.The data collection techniques used were documentation, observation, and tests. Based on the research findings, it was revealed that: (1) the planning stage involved the preparation of a teaching module with complete components based on student needs; (2) the implementation of the learning process went well, as shown by teacher activity categorized as very good with a percentage of 92.30% and student activity also categorized as very good with a percentage of 93.7%; and (3) the learning outcomes showed that 25 students achieved mastery while 1 student did not. The student learning mastery rate was categorized as very good with a percentage of 90.19%, indicating that the application of Wattpad was effective for class XI of SMA Ahmad Yani 2 Baureno.This research strongly recommends that Indonesian language teachers utilize Wattpad as an alternative medium for teaching novel review writing to enhance students’ interest, creativity, and digital literacy.Pembelajaran menulis resensi novel di kelas XI SMA Ahmad Yani 2 Baureno kurang efektif karena pembelajaran masih menggunakan metode ceramah, sehingga peneliti menggunakan aplikasi Wattpad sebagai media alternatif. Tujuan penelitian ini untuk mengetahui bagaimana perencanaan, penerapan, dan hasil belajar siswa pada pembelajaran menulis resensi novel berbantuan media Wattpad. Jenis penelitian ini adalah penelitian kualitatif. Sampel penelitian ini kelas XI SMA Ahmad Yani 2 Baureno yang berjumlah 26 siswa. Teknik pengambilan sampel dalam penelitian ini menggunakan total sampling, yaitu seluruh siswa kelas XI SMA Ahmad Yani 2 Baureno yang berjumlah 26 orang dijadikan sebagai sampel, karena jumlahnya relatif kecil dan memungkinkan untuk diteliti secara menyeluruh. Teknik pengumpulan data menggunakan teknik dokumentasi, observasi, dan tes. Berdasarkan hasil penelitian diketahui bahwa (1) perencanaan berupa modul ajar disusun dengan komponen lengkap berdasarkan kebutuhan siswa, (2) penerapan pembelajaran berjalan dengan baik yang dibuktikan aktivitas guru berkategori sangat baik dengan presentase 92.30% aktivitas siswa berkategori sangat baik dengan presentase sebesar 93,7%, (3) hasil belajar siswa terdapat 25 siswa yang tuntas belajar dan 1 siswa yang tidak tuntas belajar. Ketuntasan belajar siswa berkategori sangat baik dengan presentase sebesar 90,19% atau efektif untuk diterapkan dikelas XI SMA Ahmad Yani 2 Baureno. Penelitian ini sangat direkomendasikan agar guru Bahasa Indonesia memanfaatkan media Wattpad sebagai alternatif pembelajaran menulis resensi novel untuk meningkatkan minat, kreativitas, dan literasi digital siswa.